2018
DOI: 10.1002/jcsm.12348
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cachexia impairs neural respiratory drive in hypoxia but not hypercapnia

Abstract: Background Cancer cachexia is an insidious process characterized by muscle atrophy with associated motor deficits, including diaphragm weakness and respiratory insufficiency. Although neuropathology contributes to muscle wasting and motor deficits in many clinical disorders, neural involvement in cachexia‐linked respiratory insufficiency has not been explored. Methods We first used whole‐body plethysmography to assess ventilatory responses to hypoxic and hypercapnic che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A notable limitation of the present study is that we were unable to directly measure diaphragm and respiratory function during this study. However, many prior works have noted alterations to diaphragm function in murine models of cancer cachexia including lower fiber cross sectional area, deteriorations in contractile efficiency, and altered ventilatory responses [ 18 , 40 ]. Taken together, although we did not specifically measure ventilatory function in the present study, it is plausible to infer that these same detriments to diaphragm health occurred with the onset of cachexia (~3–4 weeks [ 24 , 28 ]).…”
Section: Discussionmentioning
confidence: 99%
“…A notable limitation of the present study is that we were unable to directly measure diaphragm and respiratory function during this study. However, many prior works have noted alterations to diaphragm function in murine models of cancer cachexia including lower fiber cross sectional area, deteriorations in contractile efficiency, and altered ventilatory responses [ 18 , 40 ]. Taken together, although we did not specifically measure ventilatory function in the present study, it is plausible to infer that these same detriments to diaphragm health occurred with the onset of cachexia (~3–4 weeks [ 24 , 28 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Voluntary activation, defined as "the level of voluntary drive during an effort" [105,106] is especially diminished in older-old individuals [107][108][109] and up to one third of losses in force production capacity may be explained by voluntary activation [110]. A recent study on cancer cachexia, which clinically presents with muscle atrophy and associated motor deficits, found that impaired neural respiratory drive was a significant contributor to respiratory muscles insufficiency [111]. Based on research findings and theoretical reasoning this has led to questioning of the conceptualizing of sarcopenia as primarily being a condition tied to the muscular system.…”
Section: Discussionmentioning
confidence: 99%
“…A study in patients with stage III and IV of head and neck cancer assessed the reduction in LBM and fat mass after one month of concurrent chemo-radiation treatment and found a reduction by 71.7% and 28.3%, respectively [35]. In addition, muscle wasting is not an exclusive feature of skeletal muscle involved in locomotion, it has also been shown to affect respiratory muscles and even myocardium in patients with chronic disease-associated wasting [36][37][38]. Additionally, the progression of tumor cells, as well as cardiotoxicity induced by cancer treatment, may lead to a condition called "cardiac cachexia" that is characterized by cardiac atrophy, fibrosis, and myocardial dysfunction [39].…”
Section: Altered Energy Balancementioning
confidence: 99%